(untitled) (Quinto Sol, 2016)
This article analyses the works of the anarchist singer Martín Castro, those of gauchesque inspiration in particular. In tune with other anarchist renderings of criollismo, Castro presented the figure of the rebel gaucho as an emancipatory emblem. But unlike other cases, he also used it to launch a remarkable attack on discourses of the Argentine nation that presented it as exclusively European and “white”. Indeed, Castro’s is one of the few cases in which the criollista discourse was used to openly challenge common assumptions about the racial profile of the nation, something still very rare in the first decades of the 20th century, which anticipated later developments in the intellectual and political arenas. This article analyses Castro’s work in perspective and explores possible hypothesis on the intellectual origins of his remarkable use of the gaucho persona.